An annotated checklist of Platypodinae and Scolytinae (Coleoptera: Curculionidae) from Iran - Beaver, Roger A.; Ghahari, Hassan; Sanguansub, Sunisa (Zootaxa, 2016)
We provide an annotated checklist of species of bark and ambrosia beetles (Curculionidae: Platypodinae and Scolytinae) recorded from Iran, with information on distribution, host trees, biology and taxonomy. Two species of Platypodinae and 79 species of Scolytinae are recorded. Hypothenemus crudiae (Panzer, 1791), Scolytus koenigi Schevyrew, 1890 and Xyleborus monographus Fabricius, 1792 are recorded for the first time from Iran. Previous records of three further species are considered dubious and require confirmation.